THE CONCEPT OF UNDERGROUND SPACE DEVELOP-MENT CONTROL IN SOUTHERN BADUNG AREA - Kadek Adi Kurniawan; Rimadewi Supriharjo; Eko Budi Santoso (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2014)
Culture is a basic component of Balinese people’s lives. All development activities have a purpose relative to the culture and values implicit in the concept of the traditional Balinese spatial plan. However, with changing times, there has been development which is not accommodated in the Balinese traditional spatial concept. This development is underground space development. As a result, the status of this development is pending, based on formal and non formal policies. Besides that, this development is unseen and therefore largely unknown and its suitability to environment hasn’t been measured yet makes its sustainability status is in uncertain state. This paper addresses the concept of controlling the underground space development in the Southern Badung area based on Balinese traditional spatial concept and with a sustainable development approach.The result identified that underground space development in Kuta village was dominated by commercial development as parking lots. There are three zones identified based on suitability for underground space development in Kuta village which are low suitability zone, medium suitability zone and high suitability zone. The evaluation in terms of culture and environmental suitability showed that there were seven priority criteria in formulating the concept of its development, namely: outside of open green place, had mitigation system for disasters, outside of Tahura Ngurah Rai, outside of the coast border, outside of and not directly adjacent to the Holy Region, outside of and not directly adjacent to graves of Kuta. The main result of this research is a concept of underground space development control to create sustainable tourism in Kuta village.